Cadmium carcinogenesis and its relationship to other health effects in humans. - Nordberg, Gunnar F. (Scandinavian Journal of Work, Environment & Health, 1993)
Several different adverse health effects can be caused by cadmium exposure to humans and animals. In environmental and occupational health it is important to identify effects that occur at relatively low exposures (ie., the critical effects that are crucial for preventive action). In long-term human exposures to cadmium, effects of cadmium on the kidney have been considered to be critical effects and quantitative risk assessments of these effects have been performed on the basis of both risk modeling and direct epidemiologic observation. However, experimental and epidemiologic studies are providing increasing evidence that cadmium is carcinogenic, and this effect, which is considered to be stochastic in character, can be considered to be the critical effect. A quantitative evaluation of the cancer risk is currently difficult to make, but the preventive action against such effects is usually to limit the exposure as much as possible.